Understanding pre-service teachers' intention to adopt and use artificial intelligence in Nigerian inclusive classrooms - Adigun, Olufemi Timothy; Tijani, Faisat Adeniran; Haihambo, Cynthy K.; Enock, Simasiku Limbo (Frontiers in Education, 2025)
IntroductionThis study applied the Unified Theory of Acceptance and Use of Technology (UTAUT) to provide an understanding of the behavioral intentions of pre-service teachers in the adoption and utilization of artificial intelligence (AI) tools for educational engagement in the inclusive classroom.MethodsThe cross-sectional study collected data through a validated questionnaire from 411 pre-service teachers were analyzed with descriptive statistics such as frequency counts and simple percentage calculation, as well as inferential statistics which involved correlational analysis and Structural Equation Modeling (SEM).ResultsThe study established that effort expectancy had a positive and direct significant contribution to the perceived behavioral intention of pre-service teachers to adopt and use AI for inclusive education teaching. Technological self-efficacy had no direct contributory effect on these teachers' behavioral intention to adopt and use AI for inclusive education teaching. Technological self-efficacy did, however, have a significant positive and indirect contribution to the effect of performance expectancy and social influence on the pre-service teachers' behavioral intention to adopt and use AI for inclusive education teaching, based on their technological self-efficacy.DiscussionThe implication of findings of this study points to the exigency of a need to strengthen institutional policies and teacher preparation curricula in a manner that would advance the infusion of the use of artificial intelligence for teaching of learners with special needs.